Effect of the gas distribution system structure of a radial flow adsorber on gas distribution - WANG Hao-yu; LIU Ying-shu; MENG Yu (工程科学学报)
Uniform gas distribution in a radial flow adsorber plays an essential part in its performance. A 3D hydrodynamic and mathematical model of the radial flow adsorber was developed based on experimental studies. The effects of flow patterns, the cross-section ratio of central channel to outer channel, and the opening ratios of the central channel and the outer channel were comparatively studied by using this model. Radial inward flow was proved to have a better performance than radial outward flow, and the∏ type of inward flow is a little better than that of the Z type of inward flow. The best effect can be obtained when the cross-section ratio of central channel to outer channel is 18.9%. The radial non-uniformity of velocity decreases with the decrease of the opening ratio of the central channel, and the effect of flow distribution is better. But if the opening ratio of the central channel is too low, it will cause uneven local flow distribution and high energy consumption. The opening ratio of the outer channel has a little influence on flow distribution in the radial flow adsorber.